THE ROLE OF THE PRINCIPAL AS A SUPERVISOR IN IMPROVING THE QUALITY OF LEARNING IN SMPN 9 PAYAKUMBUH - Zahra, Fatimah Az; Husna, Annisa Ul; Hilma, Nurhayati; Hidayatullah, Rully (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to explore the role of the principal as a supervisor in improving the quality of learning at SMPN 9 Payakumbuh. Principals have an important role in educational supervision, which includes planning, observing and evaluating the learning process. Using a descriptive explanatory qualitative approach, this research explores the steps of supervision applied by the principal as well as the indicators of the success of the supervision. Data were obtained through interviews and observations, which were analyzed to understand the contribution of supervision to improving teacher competence and learning effectiveness. The results show that supervision conducted in a structured and regular manner can improve the quality of teaching and support student achievement. In addition, good communication between principals and teachers is a key factor in overcoming supervision challenges. Effective supervision plays an important role in creating a conducive learning environment, supporting innovation and improving school competitiveness.